An Avascular Niche Created by Axitinib‐Loaded PCL/Collagen Nanofibrous Membrane Stabilized Subcutaneous Chondrogenesis of Mesenchymal Stromal Cells. Issue 20 (28th August 2021) - Ji, Tian‐Ji; Feng, Bei; Shen, Jie; Zhang, Min; Hu, Yu‐Qing; Jiang, Ai‐Xia; Zhu, Di‐Qi; Chen, Yi‐Wei; Ji, Wei; Zhang, Zhen; Zhang, Hao; Li, Fen
Abstract: Engineered cartilage derived from mesenchymal stromal cells (MSCs) always fails to maintain the cartilaginous phenotype in the subcutaneous environment due to the ossification tendency. Vascular invasion is a prerequisite for endochondral ossification during the development of long bone. As an oral antitumor medicine, Inlyta (axitinib) possesses pronounced antiangiogenic activity, owing to the inactivation of the vascular endothelial growth factor (VEGF) signaling pathway. In this study, axitinib‐loaded poly( ε ‐caprolactone) (PCL)/collagen nanofibrous membranes are fabricated by electrospinning for the first time. Rabbit‐derived MSCs‐engineered cartilage is encapsulated in the axitinib‐loaded nanofibrous membrane and subcutaneously implanted into nude mice. The sustained and localized release of axitinib successfully inhibits vascular invasion, stabilizes cartilaginous phenotype, and helps cartilage maturation. RNA sequence further reveals that axitinib creates an avascular, hypoxic, and low immune response niche. Timp1 is remarkably upregulated in this niche, which probably plays a functional role in inhibiting the activity of matrix metalloproteinases and stabilizing the engineered cartilage. This study provides a novel strategy for stable subcutaneous chondrogenesis of mesenchymal stromal cells, which is also suitable for other medical applications, such as arthritis treatment, local treatment of tumors, and regeneration of other avascular tissues (cornea and tendon). Abstract : Axitinib, an oral antiangiogenic medicine, is loaded into nanofibrous membranes by electrospinning. Engineered cartilage, derived from bone marrow mesenchymal stromal cells (BMSCs), is encapsulated in the membrane and subcutaneously implanted. The sustained and localized release of axitinib successfully inhibits the vascular invasion and creates an avascular niche. Consequently, stable chondrogenesis of BMSCs is achieved in the subcutaneous environment.